2001
DOI: 10.1038/sj.ejcn.1601163
|View full text |Cite
|
Sign up to set email alerts
|

Energy density, energy intake and weight status in a large free-living sample of Chinese adults: exploring the underlying roles of fat, protein, carbohydrate, fiber and water intakes

Abstract: Surveys were used to test for associations between energy density, energy intake and weight status, controlling for age, sex, height, activity level, smoking status, urban residence and income. Pearson correlation coef®cients were calculated to identify nutrient intake correlates of energy density. Replacing energy density with its nutrient correlates (3 day mean estimates of fat, protein, ®ber and water intakes) in the models predicting energy intake and overweight status, the independent effects of speci®c n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 15 publications
8
57
2
1
Order By: Relevance
“…In the present study, energy density was inversely associated with intakes of carbohydrates and proteins, both 60.6 (57.6-63.6) 33.8 (30.7-36.8) 17.2 (14.1-20.2) 7.9 (4.9-11.0) o0.001 Cholesterol b 71.8 (68.2-75.3) 58.9 (55.3-62.4) 53.6 (50.1-57.2) 46.3 (42.7-49.9) o0.001 Fiber b 84.0 (80.8-87.3) 77.1 (73.9-80.4) 62.6 (59.4-65.9) 36.7 (33.5-40.0) o0.001 Folate b 72.4 (69.0-75.9) 59.0 (55.6-62.5) 45.0 (41.6-48.5) 28.3 (24.8-31.8 Diet quality of free selected low-energy density diets H Schröder et al expressed in a percentage of total energy intake. In contrast, a strong direct relationship was observed for energy density with energy consumption and total fat intake, which is in line with previous findings (Stookey, 2001;Crowe et al, 2004). In the present study, an increase of 10% in fat intakes was associated with a change of 0.98 kJ/g of energy density.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, energy density was inversely associated with intakes of carbohydrates and proteins, both 60.6 (57.6-63.6) 33.8 (30.7-36.8) 17.2 (14.1-20.2) 7.9 (4.9-11.0) o0.001 Cholesterol b 71.8 (68.2-75.3) 58.9 (55.3-62.4) 53.6 (50.1-57.2) 46.3 (42.7-49.9) o0.001 Fiber b 84.0 (80.8-87.3) 77.1 (73.9-80.4) 62.6 (59.4-65.9) 36.7 (33.5-40.0) o0.001 Folate b 72.4 (69.0-75.9) 59.0 (55.6-62.5) 45.0 (41.6-48.5) 28.3 (24.8-31.8 Diet quality of free selected low-energy density diets H Schröder et al expressed in a percentage of total energy intake. In contrast, a strong direct relationship was observed for energy density with energy consumption and total fat intake, which is in line with previous findings (Stookey, 2001;Crowe et al, 2004). In the present study, an increase of 10% in fat intakes was associated with a change of 0.98 kJ/g of energy density.…”
Section: Discussionsupporting
confidence: 92%
“…However, the study of dietary energy density in free-living persons is a new effort, and data on this issue are scarce. Observational studies generally found a direct association between energy intake and energy density (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Stookey, 2001;Darmon et al, 2004). All these studies mainly focused on the association between energy density with energy and macronutrient intake and in some cases, additionally, with body mass index (BMI) (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Cuco et al, 2001;Stookey, 2001;Darmon et al, 2004;Ledikwe et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
mentioning
confidence: 97%
“…Some studies have reported positive associations between ED and EI (4,10,11) . In addition, there is a strong correlation between the ED of foods and their fat content (4,12) , which may also encourage weight gain.However, the results from cross-sectional epidemiological studies that have examined the relationships between dietary ED and body-weight status are not consistent (10,13 -20) .Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
mentioning
confidence: 99%